FUNGSI HUKUM PERLINDUNGAN KONSUMEN DI INDONESIA - Ni Luh Made Elida Rani; Pande I Made Widya Adnyana (FAKULTAS ILMU AGAMA DAN KEBUDAYAAN, 2025)
Consumer protection law is a crucial area of ​​law in safeguarding the interests and rights of consumers in their interactions with producers, distributors, and service providers. Amidst the dynamics of economic development and globalization, consumer protection has become increasingly relevant in ensuring a balance of power between businesses and consumers. In this modern era, consumers have greater access to a variety of products and services, both physically and through online platforms. However, these developments also raise new challenges in the form of business practices that harm consumers, such as fraud, the sale of counterfeit products, circulating advertising, and discrepancies between product quality and promises. This article will further discuss consumer protection law, including its legal basis, principles of consumer protection, and existing law enforcement mechanisms. It will also address several current issues in consumer protection, such as consumer protection in online businesses, producer responsibility for unsafe products, and efforts to increase consumer awareness and understanding of their rights